American trypanosomiasis : Chagas disease : one hundred years of research - Tibayrenc, Michel; Telleria, Jenny (Elsevier insights., 2010)
Chagas Disease causes severe socioeconomic impact and a high medical cost in Latin America. WHO and the World Bank consider Chagas Disease as the fourth most transmittable disease to have a major impact on public health in Latin America: 120 million persons are potentially exposed, 16-18 million of whom are presently infected, causing 45,000-50,000 deaths per year. It has been calculated that approximately 2.4 million potential working years are lost because of incapacity and mortality due to the disease, for an annual cost estimated at 20 billion euros. This book provides a comprehensive overview of Chagas Disease and discusses the latest discoveries concerning the three elements that compose the transmission chain of the disease: The host: human and mammalian reservoirs ; The insect vectors: domestic and sylvatic vectors ; The causative parasite: Trypanosoma cruzi.